Studi Akumulasi Logam Tembaga (Cu) dan Efeknya terhadap Struktur Akar Mangrove (Rhizophora mucronata) - Irwan Dedy; Adi Santoso; Irwani Irwani (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro, 2013)
Copper metal (Cu) is one of the heavy metals that can contaminate the environment, especially water. Cu is a heavy metal which is harmful to human health, but Cu is also needed in our life as trace elements. This study aimed to determine the effect of Cu contaminants with different concentrations on the root structure of the mangrove seedlings Rhizophora mucronata for 30 days of observation. Rhizophora mucronata is taken from Tapak village, Tugu, Semarang, Central Java. The research was carried out from June to August 2012 at the Marine Science Campus of Diponegoro University Semarang. A laboratory experiment research was conducted on the effect of different Cu concentrationt (20, 100 and 500 ppm) and different exposure material (10, 20 and 30 days) on the root structure of mangrove Rhizophora mucronata. Root structure using microscopy observations performed at the Laboratory of Plant Faculty of Science and Mathematics, Diponegoro University. The result demonstrated that the root of epidermis, cortex, endodermis, xylem and phloem had no effect on their structure after exposure to concentration of Cu of 20, 100 and 500 ppm since there were not change on their shape compared to the control.